Inferring the evolutionary mechanism of the chloroplast genome size by comparing whole-chloroplast genome sequences in seed plants - Zheng Xiao-Ming (Nature Portfolio, 2017)
Abstract The chloroplast genome originated from photosynthetic organisms and has retained the core genes that mainly encode components of photosynthesis. However, the causes of variations in chloroplast genome size in seed plants have only been thoroughly analyzed within small subsets of spermatophytes. In this study, we conducted the first comparative analysis on a large scale to examine the relationship between sequence characteristics and genome size in 272 seed plants based on cross-species and phylogenetic signal analysis. Our results showed that inverted repeat regions, large or small single copies, intergenic regions, and gene number can be attributed to the variations in chloroplast genome size among closely related species. However, chloroplast gene length underwent evolution affecting chloroplast genome size in seed plants irrespective of whether phylogenetic information was incorporated. Among chloroplast genes, atpA, accD and ycf1 account for 13% of the variation in genome size, and the average Ka/Ks values of homologous pairs of the three genes are larger than 1. The relationship between chloroplast genome size and gene length might be affected by selection during the evolution of spermatophytes. The variation in chloroplast genome size may influence energy generation and ecological strategy in seed plants.